2021
DOI: 10.1136/bmjopen-2020-047515
|View full text |Cite
|
Sign up to set email alerts
|

Cost–utility analysis of antimicrobial stewardship programme at a tertiary teaching hospital in Ethiopia

Abstract: ObjectiveAntimicrobial stewardship (AMS) significantly reduces inappropriate antibiotic use and improves patient outcomes. In low-resource settings, AMS implementation may require concurrent strengthening of clinical microbiology capacity therefore additional investments. We assessed the cost-effectiveness of implementing AMS at Tikur Anbessa Specialised Hospital (TASH), a tertiary care hospital in Ethiopia.DesignWe developed a Markov cohort model to assess the cost–utility of pharmacist-led AMS with concurren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…The implementation of diagnostic infrastructure and antimicrobial stewardship (AMS) is not cheap [ 47 ] and involves a range of different building stones [ 48 ]. However, it might be cost-effective, considering the high price associated with rising AMR rates and the subsequent morbidity and mortality [ 7 , 49 ]. Diagnostic services therefore need to be included into publically funded health care and not be dependent on patients’ ability to pay.…”
Section: Discussionmentioning
confidence: 99%
“…The implementation of diagnostic infrastructure and antimicrobial stewardship (AMS) is not cheap [ 47 ] and involves a range of different building stones [ 48 ]. However, it might be cost-effective, considering the high price associated with rising AMR rates and the subsequent morbidity and mortality [ 7 , 49 ]. Diagnostic services therefore need to be included into publically funded health care and not be dependent on patients’ ability to pay.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported that a high rate of antimicrobial use-related problems can be prevented by implementing rational antimicrobial use programs and implementing disease-specific treatment guidelines. 21 While the positive impact of antimicrobial stewardship programs on reducing inappropriate prescribing, cost, and antimicrobial resistance is well-documented, 1 , 32 it is essential to acknowledge the challenges faced in their implementation. Similar to numerous low- and middle-income countries, the implementation of antimicrobial stewardship in Ethiopia encounters challenges like limited awareness among healthcare professionals and the public, absence of standardized guidelines, and insufficient resources; addressing these issues requires comprehensive strategies involving education, policy development, improved access to diagnostic tools, and enhanced collaboration among stakeholders to ensure effective and sustainable antimicrobial use.…”
Section: Discussionmentioning
confidence: 99%
“…These included replacing the medicine with less effective ones, reducing the amount of medicine, and encouraging patients to pay for the medicine [ 52 ]. Evidence shows that diagnostic stewardship, culture-guided antibiotic treatment [ 53 , 54 ] and prophylaxis [ 55 ], increased cost-effectiveness i.e., decreased treatment and hospitalization expenditures [ 53 , 54 ]. However, the hospitals in this study did not monitor antibiotic and infection related expenditures, providing no rationale for either investing in AMS or asking for additional resources.…”
Section: Discussionmentioning
confidence: 99%